2013
DOI: 10.1002/star.201200186
|View full text |Cite
|
Sign up to set email alerts
|

Influence of storage temperature and autoclaving cycles on slowly digestible and resistant starch (RS) formation from partially debranched rice starch

Abstract: In this study, optimum conditions to produce slowly digestible starch (SDS) and RS from rice starch were investigated as a function of pullulanase concentrations, storage temperature, and autoclavingcooling cycles. Then, the physicochemical properties of the rice starches obtained were compared with native rice starch. Response surface methodology (RSM) was used to evaluate the effects of independent variables, namely the enzyme (pullulanase) concentration (X 1 ), storage temperature (X 2 ), and autoclaving-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The inclusion of RS as a portion of dietary fiber and the interest in consuming foods with high dietary fiber content is motivated by positive contributions to the health of consumers . Additionally, an important amount of slowly digestible starch (SDS) was detected for both cross‐linked banana starches, which is an important issue because of the health benefits associated with these starch fractions .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of RS as a portion of dietary fiber and the interest in consuming foods with high dietary fiber content is motivated by positive contributions to the health of consumers . Additionally, an important amount of slowly digestible starch (SDS) was detected for both cross‐linked banana starches, which is an important issue because of the health benefits associated with these starch fractions .…”
Section: Resultsmentioning
confidence: 99%
“…Consumption of foods with a low GI has been related to the possibility of reducing the risk of chronic‐degenerative diseases associated with diet, e.g., Type‐2 diabetes, cardiovascular diseases and obesity. Therefore, understanding the digestion mechanisms of SDS and glucose delivered in the small intestine is a current topic of intense research .…”
Section: Introductionmentioning
confidence: 99%
“…It is recognized to impact gut bacteria, act as pre-and probiotics, has a role in preventing colon cancer, and help to overcome gastrointestinal dysfunction (2). RS is known to have a hypoglycemic effect, Faridah et al 10.3389/fnut.2022.904700 which can lower fasting blood glucose levels, increase insulin secretion and improve insulin sensitivity (3). According to Kumar et al (4) and Lemlioglu-Austin et al (5), the higher the content of RS in the sample, the lower the glycaemic index value produced.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies stated that the more cycles used, the higher the RS content increase (1,(9)(10)(11). However, Ratnaningsih et al (12) reported that autoclaving-cooling 1 cycle resulted in higher RS content than autoclaving-cooling with 3 cycles and 5 cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Wet heat processing has been found to increase RS as well as reduce RS in various cereal foods and this was largely attributed to differences in methods of RS assay . Nonetheless, changes in RS after heat processing are a consequence of the cooling conditions, and subsequent reheating and cooling cycles .…”
Section: Influence Of Cereal Food Processing Technologies On Starch Dmentioning
confidence: 99%